Infección de la herida quirúrgica postcesárea en el Hospital Teófilo Dávila de la ciudad de Machala en los meses de enero a diciembre del año 2010 - Zamora Orellana, Luis A. (2012)
We performed a retrospective study in the field of gynecology and obstetrics Hospital Teófilo Dávila of the city of Machala in 304 folders were reviewed income and expenses of patients without a history of hypertensive disease during pregnancy and 78 folders for patients with this history in 2010 with the aim of determining the rate of wound infection post-caesarean section in the specified period.